2017
DOI: 10.1245/s10434-017-6237-0
|View full text |Cite
|
Sign up to set email alerts
|

T-Helper 1 Immune Response in Metastatic Lymph Nodes of Pancreatic Ductal Adenocarcinoma: A Marker For Prolonged Survival

Abstract: Our data indicate an association between Th1-type immune response and increased survival. Future research is needed to exploit Th1 immune response as a biological marker for immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Therefore, the lack of progression of low grade dysplasia in KCI mice is likely due to disruption of autophagy and immune suppression that are required for progression of Kras G12D -driven pancreatic lesions to PDAC [50,82,83]. We further demonstrated that high PRKCI expression in PDAC is associated with reduced activation of several immune signaling pathways implicated in the improved survival of PDAC cancer patients, including OX40, iCOS, and Th1 signaling [84][85][86][87].…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, the lack of progression of low grade dysplasia in KCI mice is likely due to disruption of autophagy and immune suppression that are required for progression of Kras G12D -driven pancreatic lesions to PDAC [50,82,83]. We further demonstrated that high PRKCI expression in PDAC is associated with reduced activation of several immune signaling pathways implicated in the improved survival of PDAC cancer patients, including OX40, iCOS, and Th1 signaling [84][85][86][87].…”
Section: Discussionmentioning
confidence: 70%
“…6E ). The previously reported T helper (Th) 1 immune response could be used as a biological marker for immunotherapy in metastatic lymph nodes of PDAC [ 22 ]. Specifically, the interactions of Th1-mediated responses between immune cells and type 5 ductal cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, interferon gamma (IFN-Îł) produced by T h 1 cells not only has direct effects on arresting cellular proliferation, promoting apoptosis, and reducing angiogenesis but also on improving CTL responses to robust antitumor immunity [17]. Notably, T h 1 immune responses in lymph nodes signify a protective effect in colon cancer patients [27] and can be considered a marker for prolonged survival in pancreatic ductal adenocarcinoma (PDAC) patients [28].…”
Section: T Cellsmentioning
confidence: 99%